PROXY WAR BETWEEN AMERICA AND RUSSIA IN SYRIAN CONFLICT 2011-2015 - Ibrahim, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This paper is a study of Proxy war between United State and Russia in Syrian Conflict, United State and Russia have political and strategic interests in Syria, this triggers proxy war. Syria has been in conflict since the beginning of 2011. the conflict between the government and the opposition was preceded by the demands of the revolution in the government. This wave of revolution was triggered by the phenomenon of Arab Spring. however, in internal conflicts that occurred between the government and the opposition, there were outside parties who helped make the conflict more complex. The conflict of interests between America and Russia in the Syria conflict made the conflict more complex. for America, Syria is a barrier to creating security for its allies in the Middle East region.This research uses the concept of Proxy war in which both of United State and Russia support the rebel and the goverment. Supported by security complex theory that leads to qualitative research methods as well as literature study as a source of information. Security complex has four main variables, namely boundary, anarchic structure, polarity, and social structure. The four main variables has proof the conflict interest between the great power. In the conflict of the great power, Syrian conlict are used as a proxy by the United State and Russia.United State give their support to the opposisition by giving a train to the rebels. Russia that wants the regime remain the same, give their support in diplomacy way and high arm trade. To secure their strategic interest in syria, both United State and Russia keep give their support in many ways to the opposition and the regime. Syria is very important to both of United State and Russia.KeyWords: Proxy War, Strategic, Security, Military, Middle East, Security complex,Interest.